National Survey of Pharmacy Practice at MOH Hospitals in Saudi Arabia 2016-2017: Prescribing and Medication Management - Alomi, Yousef Ahmed; Jamaan Alghamdi, Saeed; Alattyh, Radi Abdullah; Shorog, Eman; Alshahran, Asma; Alasmary, Sara; Alenazi, Hadeel; Almutairi, Amani; Almutairi, Marsheal (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia 2016: Prescribing and medication management. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into eight domains drove from American Society of Health-System Pharmacists (ASHP), Saudi Pharmaceutical Society (SPS) survey, and the international standard of Joint Commission of Hospital Accreditation. The 5-point Likert response scale system was used with closed and ended questions. An electronic questionnaire was distributed to the one hundred eighty-five directors of pharmacies at MOH hospitals. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: the prescribing and medication management. Results: The survey questionnaire distributed to 185 of hospitals, the rate of reply, was 105 (56.75%) hospitals. The highest score of committee shared by the hospital pharmacy was the pharmacy and therapeutics committee (4.33), quality management committee (4.06), infection control committee (3.88), while the lowest scores were Anticoagulation committee (2.14), DUE committee (2.16) and IV therapy committee (1.99). The most therapeutic guideline available in the hospital pharmacies were antibiotics guidelines (2.91) followed by infection control (2.84) and anticoagulation guidelines (2.13). The majority formulary management method used was restricted prescribing certain expensive drugs 33 (33.1%), review of non-formulary drugs prior approval 27 (25.7%), and the closed drug formulary 14(13.3%). The most drug utilization activities used at the hospitals were Used as the basis for revision of drug-use policies and procedures 44 (41.9%) and Incorporated into medical staff credentialing considerations 27 (25.7%) The pharmacist has the privilege to write medication orders were 18 (17.1%) only. The pharmacist commonly prescribed over the counter medications 19 (57.6%) and antibiotics 15 (45.5%) through the prescription cosigned by physician 55 (52.4%). Followed by Drugs under prescribing protocol 39 (37.1%) and Medications Refill Clinic 26 (24.8%). Conclusion: The hospital seldom participated in the therapeutic guidelines, and the few pharmacists shared in essential hospital committees despite the unique role of providing medication information. Expanding pharmacy activities will improve the prescribing system, patient clinical outcomes, and prevent drug misadventures.
Keywords: Prescribing; Medication management; Ministry of health; Saudi arabia